Development of water protection of Lake Onega - Podsechin, Victor; Kaipainen, Heikki; Filatov, Nikolai; Bilaletdin, Ämer; Frisk, Tom; Paananen, Arto; Terzhevik, Arkady; Vuoristo, Heidi (Pirkanmaa Regional Environment Centre, 2013)
Lake Onega is the second largest lake in Europe after Lake Ladoga. The lake is located in the Karelian Republic, in the Leningradskaya and Vologodskaya regions of the Russian Federation. The area of the lake is 9800 km2, its max depth is 127 m and the average depth about 30 m. The main cities situated on the shore of the lake are Petrozavodsk and Kondopoga. The lake is connected to the Baltic Sea via the River Svir, Lake Ladoga and the Neva River. Russia is not joining the European Union (EU) in the near future. However, there is tendency to adopt the central principles of many EU directives also in Russia. Water Framework Directive (WFD) is a useful directive giving the main guidelines about how to organize water management. The aim of the project was to make an investigation of the status of Lake Onega, to assess pressures and risks into the lake and make a general plan for water protection to guarantee a good chemical and ecological status of the lake, as expressed on the WFD. One purpose of this project was to transfer Finnish knowledge and results of Finnish investigations concerning the WFD to the area of Lake Onega. In this study, many different steady-state and dynamic catchment and water quality models were used in assessing the effects of different loading scenarios. While Lake Onega preserves a good status of water as a whole, the problems with pollution and eutrophication exist in Petrozavodsk and Kondopoga Bays where anthropogenic loading is more pronounced. The excessive phosphorus loading with Petrozavodsk wastewaters should be reduced considerably to prevent further eutrophication of Lake Onega. The existing treatment removes about 55-60% of total phosphorus from Petrozavodsk wastewaters. Modern technology permits to increase this figure up to 95%. In Kondopoga Bay anthropogenic impact is most severe, the pollution is heaviest at the head of the bay throughout the year, where Kondopoga PPM withdraws wastewaters for nearly 80 years (40 years without treatment). To improve environmental conditions ...